The relationship celebrity endorsement in cosmetic advertisement towards the brand loyalty in Klang Valley / Norafifi Samat - Samat, Norafifi (Faculty of Business and Management, 2014)
In the world of advertising, there are a lot of ways to express, to convey message and to deliver information to the consumer. Advertising plays an important role in any business and become one of the keys to effective product promotion. With the existence of so many communication media existed today, people are being exposed to advertising almost every day and almost everywhere. Celebrity endorsement is one of the strategies which companies frequently used to promote the brand thus enhances sales and ultimately increase market share. Celebrity endorser is a person who enjoys high reputations and prestige, and being known to most people. In addition, celebrity is a relevant strategy for the product categories which improves the image which cosmetic product. This is especially common in highly competitive cosmetic industry. In this study, relationship on brand loyalty of different factors of celebrity endorsement in cosmetic market was investigated. Trustworthiness, expertise, attractive, respect, and also similarity is independent variable element in celebrity endorsement that have been investigated in this study. In order to provide a guide in this study, five hypotheses were formulated. Data were collected from 60 respondents using the questionnaire and the results was analyzed using SPSS to find the significant relationship between independent variable and dependent variable.